Prune-Belly syndrome in 2 cases seen in a tertiary medical institution Southeast Nigeria – A case report - Uzoamaka, Muoneke Vivian; Ikenna, Nwokoye; Obumneme, Ezeanosike; Benson, Onyire Nnamdi; Linda, Nwokeji-Onwe; Olapeju, Daniyan; Olugbenga, Oduneye (Indian Journal of Child Health, 2019)
Prune-Belly syndrome is a rare congenital disorder, and in underdeveloped and developing countries, the outcome is not well known as only a few isolated cases have been reported. A review of 2 male neonates admitted and managed for Prune-Belly syndrome in the neonatal unit of the Pediatric Department of the Federal Teaching Hospital of Nigeria. This appears to be the very first of such cases to be seen at this hospital. Both babies were delivered outside this tertiary institution and eventually referred here for proper diagnosis and management. Two male neonates aged 2 and 3 days, respectively, were admitted in the same month with a common history of maternal febrile history, poor cry on delivery, and oligohydramnios in one of them. Clinical examination showed scaphoid, lax, and wrinkled abdomen with visible peristalsis and flank fullness, ballotable kidneys, distended bladder, well-formed phallus, small scrotum, and absent testes. There were also musculoskeletal abnormalities ranging from lower limb dysgenesis to clubbing of the feet. Prune-Belly syndrome presents with a spectrum of features which present an overwhelming challenge to both the parents and the managing physician, especially in most resource-poor countries.